Eccentric training interventions and team sport athletes - McNeill, C.; Beaven, C. M.; McMaster, D. T.; Gill, N. (Journal of Functional Morphology and Kinesiology, 2019)
Eccentric resistance training has been shown to improve performance outcomes in a range of populations, making it a popular choice for practitioners. Evidence suggests that neuromuscular adaptations resulting from eccentric overload (EO) and accentuated eccentric loading (AEL) methods could benefit athletic populations competing in team sports. The purpose of this review was to determine the e ects of eccentric resistance training on performance qualities in trained male team sport athletes. A systematic review was conducted using electronic databases PubMed, SPORTDiscus andWeb of Science in May 2019. The literature search resulted in 1402 initial articles, with 14 included in the final analysis. Variables related to strength, speed, power and change of direction ability were extracted and e ect sizes were calculated with a correction for small sample size. Trivial, moderate and large e ect sizes were reported for strength (..0.17 to 1.67), speed (..0.08 to 1.06), power (0.27 to 1.63) and change of direction (0.48 to 1.46) outcomes. Eccentric resistance training appears to be an e ective stimulus for developing neuromuscular qualities in trained male team sport athletes. However, the range of e ect sizes, testing protocols and training interventions suggest that more research is needed to better implement this type of training in athletic populations.